Notes sobre trets dialectals en el «Llibre de les costums de Tortosa» - Duarte i Montserrat, Carles (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: An analysis of dialectal characteristics of this text allows the author to put forth the hypotesis of the existence of common arabisms in the most arabized territories while they ara almost inexistent in teh rest of the Catalonian linguistic dominion.